Results-based management model to improve the modernization of public management in Peruvian local governments - Lozano Rios, Marco Antonio (2024)
The objective was to determine a results-based management model to improve the modernization of public management in the District Municipality of Jepelacio in 2024. This is an applied, non-experimental, quantitative approach, cross-sectional, descriptive and propositional study, with a population of 51 workers and a sample of 39, to whom the survey technique and the questionnaire technique were applied as an instrument. Results: management by results was characterized as medium level with 50.98 %, and its dimensions are planning (50.98 %), program management (47.06 %), financial-budgetary management (50.98 %), monitoring and evaluation (49.02 %), and the characteristics of the modernization of public management indicate that it is at a medium level with 52.94%, and its dimensions are administrative simplification (52.94%), administrative areas (54.90%), management by processes (47.06%), and citizen participation (60.98%). In conclusion, the results-based management model to improve the modernization of public management is based on process optimization, quality management, and capacity building.